The dilemma between management control and innovation : a case study of Kunnskapsparken Nord AS - Jensen, Are (Universitetet i Nordland, 2012)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2012 The purpose of this research is to explore the role of management control in an innovation context. Studying a business incubator, its two largest owners, and two entrepreneurial firms connected to the incubator, I find that the role of management control differs for the actors involved. Data was collected through an introductory document study and interviews. I found that outcome based controls are not utilized due to the negative perceived effects this form of control can have on development work. Behavioural control on the other hand is extensively used. When dilemmas between control and the development of innovations occur in the incubator, trust acts as a mediating factor creating an “outer room of action” in which renegotiations of the aims of the controls take place. Two mobilization effects in the two entrepreneurial firms connected to the incubator are also observed and analysed. Their difference in age, size and stage of development seems to influence how management control is used both for coordination but also for improving the innovation process. My research has implications for the research on management control’s role in development work, as well as for businesses wanting to enter into relationships with entrepreneurial firms.